Pendidikan promosi kesehatan tentang kejadian diare di Puskesmas Kecamatan Tanjung Karang Pusat Bandar Lampung - Rifaie, Mahda Rizka Faer; Zainaro, M. Arifki; Gunawan, M. Ricko (JOURNAL of Public Health Concerns, 2025)
Background: Diarrhea in children is a leading cause of death, mostly due to infection. A child is categorized as having diarrhea if the volume of stool exceeds 10 ml/kg/day. The prevalence of diarrhea in children reaches 7.4%. In Bandar Lampung City, 5.754 cases of diarrhea in children were recorded. Of the three sub-districts in Tanjung Karang, Tanjung Karang Pusat District ranked first with 261 cases of diarrhea in children in 2024. This situation indicates the need for effective health promotion efforts to increase public knowledge regarding diarrhea prevention and treatment. Purpose: To increase knowledge about diarrhea incidence through health promotion media using leaflets and community health education programs (CHEP). Method: This study employed a quantitative design with a Paired Sample T-Test approach. The study population consisted of respondents in Tanjung Karang Pusat District. Most respondents were aged 31–40 years and had a senior high school education level. Knowledge levels were measured before and after the health promotion intervention using leaflets and community health education programs (CHEP).. Results: This activity was conducted on June 20, 2025, in the Tanjung Karang Pusat District Health Center, Bandar Lampung City. Participants were 30 parents with toddlers in the Tanjung Karang Pusat District Health Center's work area. Inclusion criteria were those who were willing to participate, had toddler-aged children, and were able to read. The instruments used were a questionnaire to measure respondents' knowledge and leaflets as reading materials during the presentation. The activity was conducted using a lecture method and provided instructions using leaflets. Measurement of the effectiveness of health education through health promotion media on parents' knowledge about diarrhea in children was conducted before and after the outreach activity. Results: The respondents' pre-test score averaged 64.30 with a standard deviation of 9.9 within a range of 50-80, with a 95% CI for Mean of 60.58-68.02. The post-test score averaged 83.67 with a standard deviation of 9.6 within a range of 70-100, with a 95% CI for Mean of 80.07-68.02. Conclusion: Health education through health promotion media in the form of leaflets and outreach programs (OPU) significantly improved parents' knowledge about diarrhea, prevention, and post-diarrheal care in children. Suggestion: It is hoped that health workers at community health centers (Puskesmas) will adopt media-based health education methods such as leaflets, community health education programs (CHEP), and interactive digital promotional methods on a regular basis to reach a wider audience. Keywords: Community health center; Diarrhea; Health education promotion; Leaflets Pendahuluan: Diare pada anak merupakan salah satu penyebab utama kematian yang sebagian besar disebabkan oleh infeksi. Seorang anak dikategorikan mengalami diare apabila volume buang air besar lebih dari 10 ml/kg/hari. Prevalensi diare pada anak mencapai 7.4%. Di Kota Bandar Lampung, tercatat 5.754 kasus diare pada anak. Dari tiga kecamatan di Tanjung Karang, Kecamatan Tanjung Karang Pusat menduduki peringkat pertama dengan jumlah 261 kasus diare pada anak pada tahun 2024. Kondisi ini menunjukkan perlunya upaya promosi kesehatan yang efektif untuk meningkatkan pengetahuan masyarakat terkait pencegahan dan penanganan diare. Tujuan: Untuk meningkatkan pengetahuan tentang kejadian diare dengan media promosi kesehatan menggunakan leaflet dan satuan acara penyuluhan (SAP). Metode: Kegiatan ini dilaksanakan pada tanggal 20 Juni 2025 di wilayah kerja Puskesmas Kecamatan Tanjung Karang Pusat, Kota Bandar Lampung. Pesertanya adalah 30 orang tua yang memiliki balita di wilayah kerja Puskesmas Kecamatan Tanjung Karang Pusat, Kota Bandar Lampung. Kriteria inklusi adalah mereka yang bersedia menjadi responden, memiliki anak usia balita, dan mampu membaca. Instrumen yang digunakan adalah berupa lembar kuesioner sebagai alat ukur pengetahuan responden dan media leaflet sebagai media baca pada waktu penyampaian materi. Kegiatan dilakukan dengan metode ceramah dan memberikan petunjuk dengan media leaflet. Pengukuran efektivitas pendidikan kesehatan melalui media promosi kesehatan terhadap pengetahuan orang tua tentang diare pada anak dilakukan sebelum dan sesudah kegiatan penyuluhan. Hasil: Menunjukkan bahwa skor pre-test responden mendapatkan mean 64.30 dengan standar deviasi 9.9 dalam rentang 50-80 pada nilai CI for Mean(95%)=60.58-68.02, sedangkan skor post-test responden mendapatkan mean 83.67 dengan standar deviasi 9.6 dalam rentang 70-100 pada nilai CI for Mean(95%)=80.07-68.02. Simpulan: Pendidikan kesehatan melalui media promosi kesehatan berupa leaflet dan satuan acara penyuluhan (SAP) secara signifikan mampu meningkatkan pengetahuan orang tua tentang kejadian diare, pencegahan dan penangan pasca kejadian diare pada anak. Saran: Diharapkan tenaga kesehatan di puskesmas dapat mengadopsi metode pendidikan kesehatan berbasis media promosi seperti leaflet, satuan acara penyuluhan (SAP) dan metode promosi digital yang interaktif secara rutin agar dapat menjangkau kelompok yang lebih luas.